Influence of tillage and sunnhemp mulching on runoff, soil loss and sorghum (Sorghum bicolor) yield* - NARAYAN, DEV; TIWARI, A K; LAL, B; KATIYAR, V S (The Indian Journal of Agricultural Sciences, 2011)
A field study was conducted during kharif seasons of 1998 to 2001 on 27 runoff plots at 2% slope in red soils of Bundelkhand to find out a suitable tillage based package of practice for increasing the growth and yield of sorghum. Results indicated that lowest grain yield of 169 kg/ha was obtained under zero tillage, without mulching and weeding which increased to 419 kg/ha with in situ surface mulching of sunnhenlp at 25 days after sowing. Yield increased considerably under shallow tillage with one weeding to the tune of 1 420 kg/ha, it further increased to 1 625 kg/ha with surface mulching. The grain yield was further increased to 2 253 kg/ha under deep tillage and increased weeding intensity and with surface mulching, yield of sorghum increased to the highest level (2 387 kg/ha).The results of this study indicated that deep tillage based package of practice ( deep tillage + in situ surface mulching of sunnhemp -i- 2 weedings ) were found suitable for minimizing runoff. increasing profile moisture conservation and obtaining higher yield of sorghum under rainfed conditions in red soils.